Impact of intangible location attributes on residential property value in Nigeria - Aliyu, Aliyu Ahmad (2012)
Urban violence in the form of ethnic and religious crises and even open warfare has been on the increase in many African cities in the recent years. Observation from literature shows that the role of intangible location attributes as mobilising agents are among the most important questions of this century as conflicts linked to ethnicity and religion have led to significant destruction of life and residential properties. Due to the number of crises in Jos metropolis over the last two decades, there has been a process of residential segregation along religious lines, dividing the city into predominantly Christian and Muslim areas. This thesis, therefore, attempts to examine the impact of intangible location attributes on the values of residential properties in Jos metropolis, Nigeria. Data were collected by interviews, self-administered surveys through questionnaire and direct observation. The stratified random sampling technique was employed in order to generate the data needed for the research. 1000 respondents and 10 consultancy firms were selected among the occupiers of residential properties and estate firms respectively, which form the sample size for the research. However, out of 1000 and 120 questionnaires administered to the respondents and estate firms respectively, only 876 and 110 were retrieved back. Simple percentage distribution tables, charts, graphs, thematic analysis, photographs and narrations among others were used to analyse the data for the research. The findings of the research revealed that intangible location attributes are the main indicators that influence the values of residential properties in the study area. It has also been established through the findings of this research that the intangible attributes of location have great implication on the values of residential properties in the study area. The results of the analysis show that there is relationship between intangible location attributes and provision, availability and maintenance of neighbourhood facilities in the study area. The research has contributed immensely to the existing body of knowledge on residential property value indicators by introducing intangible location attributes as additional and new phenomena that influence the values of residential properties in the study area. The research has thrown up challenges, especially in linking the importance of intangible location attributes in determining residential property value with construction and real estate management, valuation, and project development appraisal. There is an utmost need on the part of the estate surveyors and valuers and real estate appraisers to take into account intangible location attributes when carrying out valuation or feasibility and viability appraisals respectively in the study area. There is also a need on the part of the investors and property developers to take into consideration intangible attributes of location whenever they want to embark on real estate investment to avoid wasting of capital.